2018
DOI: 10.1038/gim.2018.17
|View full text |Cite
|
Sign up to set email alerts
|

Genetic disorders and mortality in infancy and early childhood: delayed diagnoses and missed opportunities

Abstract: Purpose Infants admitted to a level IV neonatal intensive care unit (NICU) who do not survive early childhood represent a population likely enriched for rare genetic disease; we therefore characterized their genetic diagnostic evaluation. Methods This is a retrospective analysis of infants admitted to our NICU between January 1, 2011 and December 31, 2015 who were deceased at the time of records review with an age at death of less than five years. Results 2,670 infants were admitted; 170 later died. 106/17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 36 publications
1
64
0
1
Order By: Relevance
“…Furthermore, the high mortality in our patients who died prior to six months of age (61.73%, 50/81) indicated that genetic diseases were the common causes in early life death. This is consistent with previous studies (Jacob et al, 2015;Wojcik et al, 2018;Marshall et al, 2019). These findings explicitly established that NGS should be used as an unbiased diagnostic option for infants in NICUs (Matthijs et al, 2016;Sawyer et al, 2016) in China.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the high mortality in our patients who died prior to six months of age (61.73%, 50/81) indicated that genetic diseases were the common causes in early life death. This is consistent with previous studies (Jacob et al, 2015;Wojcik et al, 2018;Marshall et al, 2019). These findings explicitly established that NGS should be used as an unbiased diagnostic option for infants in NICUs (Matthijs et al, 2016;Sawyer et al, 2016) in China.…”
Section: Discussionsupporting
confidence: 92%
“…The most recent study regarding the contribution of genetic disease to mortality in a level IV NICU in Boston retrospectively analyzed data from 2,670 infants admitted between 2011 and 2015, 170 of whom died. Of those, 47 (28%) had a laboratory‐confirmed genetic diagnosis, 30% of which (14/47) were only made postmortem (Wojcik et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The persistence of diagnoses reached through CMA and other genetic testing modalities (e.g. methylation studies) across the study period emphasises the ongoing utility of these tests and the need for careful consideration in selecting patients in whom WES should be performed as a first‐tier sequencing test . A total of 55 NICU patients were assessed as likely having a genetic condition in 2015, and a diagnosis was made in 20 using testing modalities other than WES.…”
Section: Discussionmentioning
confidence: 99%